A five line distributed feedback dye laser - Khan, N.; Hall, T.A. (2003)
A multiple grating distributed feedback dye laser is described where laser emission is produced in a dye solution by the interference patterns of two pairs of frequency doubled Nd:YAG laser beams. Two pairs of pulses can induce five gratings that support oscillation of five lines and three pairs of pulses are expected to induce nine lines. The maximum number of laser lines depends upon the number of pump pulses and the time delay between the adjacent pairs of beams. For two pairs of excitation beams, derived from the same source through wave-front or amplitude phase division techniques, the output lasing lines varied from two to a maximum of five as the delay between the pairs of pump pulses is varied. © 2003 Elsevier B.V. All rights reserved.